Cotton Yield and Potassium Use Efficiency as Affected by Potassium Fertilizer Management with Stalks Returned to Field. Issue 2 (1st March 2016) - Yang, Fuqiang; Du, Mingwei; Tian, Xiaoli; Eneji, A. Egrinya; Li, Zhaohu
Abstract : Widespread potassium (K) deficiencies in cotton ( Gossypium hirsutum L.) have been documented throughout cotton producing countries. Potassium fertilizer is needed for high production of cotton yield. This study was conducted to determine whether K fertilizer management can improve efficiency of K nutrition in cotton. The effects of K source, rate, and application timing on yield and K use efficiency of cotton were investigated under conditions of cotton‐stalk recycling to the field in the North China Plain (NCP). The results showed that there was no significant difference in yield between K sources of K2 SO4 and KCl. However, we found that the low rate produced a 2 to 4% higher K agronomic efficiency (AEK) and a 12 to 93% higher K apparent recovery efficiency (REK) than the other rates, although there was little difference in yield among different K rates (45, 90, and 180 kg K2 O ha −1 ). In addition, our results of application timing showed that the later split application at peak bloom acquired the highest lint yield as well as a 35 to 103% higher AEK and 23 to 58% higher REK than the earlier split application at peak squaring and full dose at preplanting. In conclusion, KCl should be the preferred K source because of its lower cost and fair effect on yield compared with K2 SO4 . The 45 kg K2 O ha −1 of K rates is adequate for cotton in the NCP. The later split application of K at peak bloom is the best timing of K fertilizer for cotton yield and K use efficiency.